Estimating sampling sufficiency to evaluate infestation intensity of Diatraea spp. in sugar cane - Silva, José Antônio Aleixo da; Campos, Adriana Lira de; Veiga, Antônio Fernando Souza Leão da; Moreira, Alberto Fábio Carrano; Marques, Edmilson Jacinto (Pesquisa Agropecuaria Brasileira, 1997)
Six plot size consisting of 10, 20, 40, 60, 80 and 100 sugar cane stalks, variety CB 45-3, were compared by the relative efficiency (ER%) test to estimate infestation intensity caused by Diatraea spp. The variables used for calculating the ER% were the number of plots representing the population, mean of total time to evaluate each plot (collecting stalks in the field, opening and counting the number of damaged stalks), and the sampling error. The plot size composed of 20 stalks per hectare was selected as the most efficient.